Comparative Analysis Model for The Degree of Health Vulnerability To Air Pollution - Mihaela Adina MATEESCU; Mihai SabinMUSCALU; Elena Manuela ISTOC; Daniela Nicoleta BALEANU (Communications of International Proceedings, 2023)
This paper presents a study to evaluate the position of Romania in relation to the other  EU countries regarding the degree of human health vulnerability to air pollution.  We choose to write this study because human health and environmental health are in an interconnected relationship and it is necessary to evaluate the impact of air pollutants on public health in order to make decisions about the management of the emissions that pollute the air. The paper is based on building synthetic indicators, this is a complex process that involves the selection of different methods, tools, techniques, and variables.
Keywords: environment; air pollution; human health vulnerability